WACANA TEODISE: MENELISIK PROBLEM KEJAHATAN DAN PENDERITAAN SERTA KEADILAN TUHAN DALAM PERSPEKTIF HINDU - Siswadi, Gede Agus (UHN IGB Sugriwa Denpasar, 2023)
This research describes the problems of evil and suffering that exist in this universe. Questions about the source of evil and suffering throughout the history of philosophy and human civilization have always been a debate between people who believe in God and people who do not believe in God. If God exists, how can there be evil, where evil comes from, does God cause evil and suffering. That is the important point that will be discussed in this article. The method used in this research is a philosophical hermeneutic method. This study indicates that the source of evil and suffering described by philosophers is not from God. Humans have the freedom to choose and, at the same time, have the burden of being responsible for the choices of their liberty. In Hinduism, it is explained that God is a witness to what humans do. Humans who realize the nature of God within themselves will not fall into the choice to do evil. Humans are entangled in problems and suffering because humans forget these principles.